The Attitude between State, Society, and Human in the Book of “Al-Adab al-Kabir” (The Book of Great Etiquette) by Ibn Al-Muqaffa (International Journal of Psychosocial Rehabilitation, 2020)
This article examines Ibn al-Muqaffa's Al-Adab al-Kabir, one of the great works of Islamic philosophy and science, and its socio-philosophical significance. It is known that in the history of philosophical thought many works were written on the rulers, their attitude with the people, a just society, and social cooperation. Al-Adab al-Kabir provides detailed information on the socio-political environment of the Arab Caliphate in the VIII century, the achievements and shortcomings of the rulers, and differs from other works in this field with its peculiarity. During the process of reading this article, a clear notion appears about the righteous ruler, his moral qualities, and the relationship of him with society and the people.